Family Functioning in Accompanying Emotional Attitudes of Adolescents in Tanjung Pering Village, North Indralaya, Ogan Ilir Regency - Pratiwi, Redna; Waty, Evy Ratna Kartika (Journal of Psychology and Sustainable Education, 2025)
This study aims to determine the level of family functioning in assisting adolescents' emotional attitudes in Tanjung Pering Village. This study uses a quantitative method with a descriptive approach. The sampling technique uses saturated sampling with a total of 37 parents. Data collection was carried out through questionnaires and observations. The measurement of family functioning in Tanjung Pering Village, North Indralaya, Ogan Ilir Regency was carried out by considering eight family functions: religious functions, protection, love, socialization and education, socio-cultural, economic, reproductive, and environmental development. The study results showed that parents who assisted adolescents' emotional attitudes in Tanjung Pering Village were classified as good in each function. This is evidenced by the percentage of the overall average score of 66.62%. In the function of love, it obtained 65.37%, and the economic function obtained a percentage of 68.78%. In the reproductive function, it obtained a percentage of 65.63%, and environmental development obtained a percentage of 66.21%. However, of the eight functions, 1 of them obtained the lowest percentage score, namely the socio-cultural function of 57.09%, because parents have considered teenagers not to be small children who must be guided and taught moral values ​​​​anymore, do not always have to be regulated in everyday dress, do not need to be taught the customs of their environment until they are regulated to choose to admire someone to be an idol. Then, 29 respondents believe teenagers can carry themselves, distinguish good and bad values ​​​​, and are free to choose role models they admire.